A nationwide survey on central nervous system multiple myeloma in Japan: analysis of prognostic and treatment factors that impact survival. (28th July 2021) - Yamashita, Takeshi; Takamatsu, Hiroyuki; Kawamura, Koji; Sunami, Kazutaka; Hagiwara, Shotaro; Itagaki, Mitsuhiro; Takahashi, Tsutomu; Kondo, Tadakazu; Ikeda, Takashi; Watakabe‐Inamoto, Kyoko; Handa, Hiroshi; Imaizumi, Yoshitaka; et al.
Summary: This nationwide multicentre retrospective study was performed to analyze clinical features that predict the prognosis of central nervous system invasion in multiple myeloma (CNS‐MM, approximately 1% of MM). Overall, of the 77 adult patients with CNS‐MM identified between 2005 and 2016, those diagnosed at MM diagnosis ( n  = 3) had longer overall survival (OS) than those diagnosed at relapse ( n  = 74; median: 48·5 vs 2·7 months). Therefore, we compared the relapsed MM with CNS‐MM in patients with any treatment ( n  = 60). Multivariate analyses revealed that lenalidomide treatment [hazard ratio (HR) 0·27, P  = 0·003], intrathecal chemotherapy (IT; HR 0·54, P  = 0·05), and radiation therapy (RTx; HR 0·33, P  < 0·001) for CNS‐MM had a positive effect on longer OS. These factors were used to develop a scoring system combining the number of treatments with lenalidomide, IT, and RTx (0, 1, 2, 3). The OS of CNS‐MM patients was stratified based on these factors, with a median OS of 1·1, 4·5, and 7·5 months for patients with zero, one, two to three favourable features, respectively (0 vs 1, P  = 0·0002; 1 vs 2–3, P  = 0·08). Multimodal treatment including lenalidomide in addition to conventional IT and RTx can improve OS.